A comprehensive investigation of sperm DNA damage and oxidative stress injury in infertile patients with subclinical, normozoospermic, and astheno/oligozoospermic clinical varicocoele. (24th May 2016) - Ni, K.; Steger, K.; Yang, H.; Wang, H.; Hu, K.; Zhang, T.; Chen, B.
Summary: One of the main pathogeneses of varicocoele and infertility is oxidative stress (OS), nevertheless, the oxidative damaged DNA in infertile patients with varicocoele remains poorly clarified. The objective of this study was to comprehensively investigate whether sperm DNA damage and OS injury were related with different issues of varicocoele. According to the varicocoele practice guidelines, surgical treatment was not indicated in the infertile patients with subclinical (SubVc, n  = 15) and normozoospermic clinical varicocoele (NCVc, n  = 22), the infertile astheno/oligozoospermic patients with clinical varicocoele (AOCVc, n  = 51) would receive microsurgerical varicocoelectomy. Normozoospermic healthy donors with proven fertility ( n  = 25) were recruited as controls. Thiobarbituric acid and sperm chromatin structure assay (SCSA) methods were preformed to analyze seminal lipid peroxidation product malondialdehyde (MDA) and sperm DNA fragmentation index (DFI). We found that AOCVc and NCVc, except SubVc, could significantly elevate sperm DFI and seminal MDA levels. Varicocoelectomy could substantially improve semen parameters, and reduce sperm DFI and seminal MDA levels in the AOCVc patients. However, the non‐operative NCVc patients would possibly suffer a severe deterioration of semen parameters accompanied by aberrantly higher levels of sperm DFI and seminal MDA, whereas no differences occurred in the non‐operative SubVc patients. Sperm DFI level in the pregnant group was much lower compared to the non‐pregnant group (AOCVc, p  < 0.01; NCVc, p  < 0.05) with the best cutoff value of 19.73%, while no differences in seminal MDA ( p  > 0.05) could be observed. Finally, a strong positive correlation was found between sperm DFI and seminal MDA (Rs = 0.504, p  < 0.01), and they were also closely correlated with crucial semen parameters except normal morphology. Therefore, sperm DNA damage in clinical varicocoele, but not in SubVc, might be associated with the role of seminal reactive oxygen species (ROS) in mediating such damage. Varicocoelectomy could be beneficial for reducing OS injury and sperm DFI, and males with low sperm fragmented‐DNA level had more opportunities to become pregnant.